Α new species of Hystripαlpus (Acari: Tenuipalpidae) - Hatzinikolis Ε.Ν. (ENTOMOLOGIA HELLENICA, 1983)
The female, male, deuteronymph and larva of Hystripalpus macedonicus, new species, are described and illustrated. This mite was found on tender shoots and leaves of the olive-tree in Macedonia, Greece. Some information on the distribution and the feeding habits of the genus Hystripalpus on olive-tree is also given.